Eksperimentasi Model Gallery Walk Berbasis STEM untuk Meningkatkan Kemampuan Penalaran Matematis - Apriliana, Shela; Setiaji, Heru Agni (Jurnal Riset Pembelajaran Matematika, 2025)
This study aims to examine the effectiveness of the STEM-based Gallery Walk learning model on improving students' mathematical reasoning at MTs NU Al-Hidayah Kudus. The method used was a pseudo-experiment with a Pretest-Posttest Control Group Design. Cluster random sampling was applied in sample selection, where class VII B was the experimental class and class VII A was the control class. The research instrument was in the form of description questions based on mathematical reasoning indicators, and had been tested for validity, difficulty level, distinguishing power and reliability. Data analysis used binomial testing, Mann-Whitney U, and N-Gain calculation. As a result, the experimental class achieved classical completeness of 86%, more than the set limit of completeness (75%). The Mann-Whitney U test showed that the average value of mathematical reasoning improvement of the experimental class was more than the average value of mathematical reasoning improvement of the control class. The N-Gain calculation shows an increase of 76.5% which is categorized as effective. This means that the STEM-based Gallery Walk learning model is proven effective in improving students' mathematical reasoning skills. Thus, this model can be recommended as an alternative innovative teaching strategy to improve mathematical thinking skills.